The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.14429/dsj.61.556
|View full text |Cite
|
Sign up to set email alerts
|

LIDAR for Detection of Chemical and Biological Warfare Agents

Abstract: Remote detection of chemical and biological warfare agents and toxic gases in the atmosphere is of current interest to both the military and civilian agencies. Out of all currently available techniques, no single technique provides efficient detection against such threats at significant standoff distances. Light detection and ranging (LIDAR) technologies, based on the transmission of laser pulses and analysis of the return signals, have demonstrated impressive capabilities in remote detection of such toxic che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The concentration of the target gas can be measured by detecting the difference between the returned signals of the two lasers [16]. Assuming the transmitted power is P t , the overall system efficiency is η, the telescope receiving area is A, the distance of the hard target is R, the reflectivity of the hard target is ρ, the absorption cross-sections of λ on and λ off are σ on and σ off , the atmospheric attenuation coefficient is α and the number concentration of the molecule is N(R), then the energy P received by the detector can be expressed as [17][18][19]:…”
Section: Dial Theorymentioning
confidence: 99%
“…The concentration of the target gas can be measured by detecting the difference between the returned signals of the two lasers [16]. Assuming the transmitted power is P t , the overall system efficiency is η, the telescope receiving area is A, the distance of the hard target is R, the reflectivity of the hard target is ρ, the absorption cross-sections of λ on and λ off are σ on and σ off , the atmospheric attenuation coefficient is α and the number concentration of the molecule is N(R), then the energy P received by the detector can be expressed as [17][18][19]:…”
Section: Dial Theorymentioning
confidence: 99%
“…In terms of assessing the war's damage caused to the environment, remote sensing data have shown the ability in detecting and indicating the impact of war on the environment For example, Veerabuthiran in 2011 used the LIDAR data for detection of biological warfare agents and toxic gases in the atmosphere [58]. Reuveny in 2010showed in his study the effects of warfare on the environment [59].…”
Section: Remote Sensing Rule In Studying the Conflictsmentioning
confidence: 99%
“…Additionally, the detection of the precursors and degradation products of these materials can be equally important [3]. Existing technology has shown that these devices can effectively detect such analytes, but requires high-tech, expensive, and large instrumentation, which makes them less than ideal for field applications [4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%